2007
DOI: 10.1371/journal.pone.0000467
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Evolution of a Non-Biological Protein: Importance of Surface Residues in Protein Fold Optimization

Abstract: Phylogenetic profiling of amino acid substitution patterns in proteins has led many to conclude that most structural information is carried by interior core residues that are solvent inaccessible. This conclusion is based on the observation that buried residues generally tolerate only conserved sequence changes, while surface residues allow more diverse chemical substitutions. This notion is now changing as it has become apparent that both core and surface residues play important roles in protein folding and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 46 publications
4
48
0
Order By: Relevance
“…ANBP shared structural features with extant proteins, including a nucleotide binding pocket similar to those found in ATP-binding proteins and a Znbinding site resembling the typical treble clef Zn binding motif (Krishna and Grishin 2004). Additional in vitro selection experiments designed to improve folding stability of ANBP revealed that surface residues are as important as those buried in the structure (Smith et al 2007). The fine tuned protein (2P09) retained the original structure but folded more stably (Fig.…”
Section: Emergence Of Protein Structurementioning
confidence: 93%
“…ANBP shared structural features with extant proteins, including a nucleotide binding pocket similar to those found in ATP-binding proteins and a Znbinding site resembling the typical treble clef Zn binding motif (Krishna and Grishin 2004). Additional in vitro selection experiments designed to improve folding stability of ANBP revealed that surface residues are as important as those buried in the structure (Smith et al 2007). The fine tuned protein (2P09) retained the original structure but folded more stably (Fig.…”
Section: Emergence Of Protein Structurementioning
confidence: 93%
“…The initially selected sequences displayed poor biophysical properties (solubility, stability) for structural studies. Further evolutionary optimization of the sequences led first to a truncated version and later to multiple amino acid substitutions [27] that improved the initially selected sequences by surface stabilizing interactions [28]. This man-made progressive amelioration of artificial ATP binding proteins may, in some way, mimic a plausible evolutionary scenario for natural protein evolution.…”
Section: Gene Duplication/fusionmentioning
confidence: 97%
“…[14] After many iter-A C H T U N G T R E N N U N G ative rounds of in vitro selection and A C H T U N G T R E N N U N G directed evolution, several proteins emerged that bound ATP with high affinity and specificity. [15,16] The three-dimensional structure (Figure 2 B) of one of these proteins has now been solved by solution NMR and X-ray crystallography, and reveals a novel zinc-nucleated a/b fold with a unique topology. [16][17][18] A fundamentally different approach to generating proteins that fold into structures with novel topologies was developed by Baker and co-workers.…”
mentioning
confidence: 99%
“…[15,16] The three-dimensional structure (Figure 2 B) of one of these proteins has now been solved by solution NMR and X-ray crystallography, and reveals a novel zinc-nucleated a/b fold with a unique topology. [16][17][18] A fundamentally different approach to generating proteins that fold into structures with novel topologies was developed by Baker and co-workers. [19] Here, a general computational strategy was developed that iterates between protein sequence design and protein structure prediction to create a 93-residue a/b protein with a novel topology.…”
mentioning
confidence: 99%
See 1 more Smart Citation